Biodiesel production from inedible animal tallow and an experimental investigation of its use as alternative fuel in a direct injection diesel engine - Oner, Cengiz; Altun, Sehmus (Elsevier Sci Ltd, 2009)
In this study, a substitute fuel for diesel engines was produced from inedible animal tallow and its usability was investigated as pure biodiesel and its blends with petroleum diesel fuel in a diesel engine. Tallow methyl ester as biodiesel fuel was prepared by base-catalyzed transesterification of the fat with methanol in the presence of NaOH as catalyst. Fuel properties of methyl ester, diesel fuel and blends of them (5%, 20% and 50% by volume) were determined. Viscosity and density of fatty acid methyl ester have been found to meet ASTM D6751 and EN 14214 specifications. Viscosity and density of tallow methyl esters are found to be very close to that of diesel. The calorific value of biodiesel is found to be slightly lower than that of diesel. An experimental study was carried out in order to investigate of its usability as alternative fuel of tallow methyl ester in a direct injection diesel engine. It was observed that the addition of biodiesel to the diesel fuel decreases the effective efficiency of engine and increases the specific fuel consumption. This is due to the lower heating value of biodiesel compared to diesel fuel. However, the effective engine power was comparable by biodiesel compared with diesel fuel. Emissions of carbon monoxide (CO), oxides of nitrogen (NOx), sulphur dioxide (SO2) and smoke opacity were reduced around 15%,38.5%, 72.7% and 56.8%, respectively, in case of tallow methyl esters (B100) compared to diesel fuel. Besides, the lowest CO, NOx emissions and the highest exhaust temperature were obtained for B20 among all other fuels. The reductions in exhaust emissions made tallow methyl esters and its blends, especially B20 a suitable alternative fuel for diesel and thus could help in controlling air pollution. Based on this study, animal tallow methyl esters and its blends with petroleum diesel fuel can be used a substitute for diesel in direct injection diesel engines without any engine modification. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Inedible animal tallow; Transesterification; Biodiesel; Alternative fuel; Diesel engine